Hydrogen Evolution Reaction: Photoinduced Electrocatalysis on 3D Flexible OsOx Quantum Dots (Adv. Energy Mater. 18/2021). Issue 18 (12th May 2021) - Du, Yuncheng; Xue, Yurui; Zhang, Chao; Liu, Yuxin; Fang, Yan; Xing, Chengyu; He, Feng; Li, Yuliang
Abstract : In article number 2100234 Yurui Xue, Feng He, Yuliang Li and co‐workers demonstrate highly uniform and dispersed osmium oxide quantum dots grown on graphdiyne (GDY). The obtained catalyst shows highly active and durable electrocatalytic hydrogen evolution reaction performance under induction. GDY can effectively prevent hole–electron recombination and facilitate charge transfer for greatly enhanced catalytic activity and stability under alkaline conditions.